Wind engineering 1st IAWE European and African Regional Conference : proceedings of the conference Wind engineering organized by the International Association for Wind Engineering and held in Guernsey on 20-24 September 1993 - Cook, N. J. (Thomas Telford, 1993)
This volume contains contributions on the following aspects of wind engineering research: wind-characteristics, exposure, simulation and environment; building aerodynamics, external and internal pressures; full-scale experiments; vehicle aerodynamics and dynamic response; mathematical modelling; aeroelastic instabilities; and more